Students' Perceptions on The Use of Mind Mapping Technique in Writing Class - Sakkir, Geminastiti; Sakkir, Rini Isnaeni (Cendekiawan Indonesia Timur, 2023)
The use of mind mapping in the EFL classroom especially in writing class is imperative to fill the educational needs of the younger generation. There are few studies conducted on students’ perceptions of using mind mapping to learn the writing English language. This research aimed to investigate the students’ perceptions of the use of mind mapping in learning the writing English process at junior high school, MTsN 2 Makassar, Indonesia. Data were collected using a questionnaire that collected a five-point Likert scale to gauge the students’ perception of the use of mind mapping in writing EFL classrooms. Findings from this research indicate that most students showed a strongly positive category according to the range of students’ perception scores. Therefore, the students have a strongly positive attitude to use mind mapping in their writing skills. The use of the mind mapping technique is very interesting to the students, so they are motivated to write a paragraph.